Disability and Spirituality - Bilge Nuran Aydoğdu (Spiritual Psychology and Counseling)
Disability as a concept has been defined and explained from different perspectives over the years and cannot be regarded just with an individual focus. It should also be considered environmentally and socially. Spirituality and religion have a significant importance culturally for people with disabilities. Therefore, the purpose of this study is to explain the term disability in detail, its religious and spiritual aspects, and the use of these concepts in the rehabilitation process. Research has demonstrated spirituality and religion to be two terms that are a powerful and effective personal resource for accepting and dealing with issues regarding disability. According to studies, individuals have furthermore reported having a disability to provide them with a benefit of gaining a different point of view toward life. Because religion and spirituality are vital psychological resources that cannot be underestimated, they have been used in rehabilitation psychology as a coping mechanism. For this reason, this paper aims to provide knowledge about the concept of disability, its relationship with religion and spirituality, and its use in rehabilitation psychology.